1988
DOI: 10.1901/jaba.1988.21-233
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Public Policy: The Case of State Legislation for Child Passenger Safety

Abstract: Observations of children in automobiles were made in seven states before and after implementation of legislation requiring use of child passenger safety devices. Increases in safe seating for children covered by state laws and children under 1 year old were observed in three of the five states implementing legislation during this study. Decreases in safe seating for these age groups were observed in two states, however. Increases in safe seating for children from 1 to 5 years old were observed in four of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…While increases in appropriate restraint use have been observed after the introduction of legislation in other jurisdictions for children aged less than four years, [22][23][24] this has not always been the case. 24,25 A US study found self-reported child restraint use did not change significantly in a low socioeconomic sample of families after the introduction of legislation specifying age-appropriate restraint use. Furthermore, they found a significant increase in premature graduation to booster seats from forward-facing child restraints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While increases in appropriate restraint use have been observed after the introduction of legislation in other jurisdictions for children aged less than four years, [22][23][24] this has not always been the case. 24,25 A US study found self-reported child restraint use did not change significantly in a low socioeconomic sample of families after the introduction of legislation specifying age-appropriate restraint use. Furthermore, they found a significant increase in premature graduation to booster seats from forward-facing child restraints.…”
mentioning
confidence: 99%
“…However, others have reported improvements in correct use with strengthened legislation. [22][23][24] We hypothesised that recent amendments to Australian legislation would have increased the use of age-appropriate car restraints across all sectors of the community. As families from low educational, lowincome and non-English-speaking backgrounds were previously seen to have the lowest compliance with optimal child restraint practices, we focused our analysis on this sector of the community.…”
mentioning
confidence: 99%
“…3 Legislation is an effective way of changing outcomes due to MVCs. Legislation regarding minimum alcohol-drinking age, 20,21 elderly licensure, 13 seat belt use, 22,23 the use of child safety seats for children from birth through 5 years, 24,25 and graduated driver licensing for teenagers [26][27][28] have decreased motor vehicle-related deaths and injuries in the United States. Similarly, our data show that, even after controlling for other motor vehicle legislation, as well as controlling for temporal and economic factors that could influence MVC fatalities in children, the enactment of booster seat laws further reduces childhood fatalities.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 256) Corruption cultures are the cumulative outcome of individual decisions that are made without regard to the consequences for the collective and hence our focus should be on changing cultural practices. Behavioral research has shown that legislation (Seekins et al, 1988), signs and prompters (Williams, Thyer, Bailey, & Harrison, 1989), and signed promise cards (Geller & Lehman, 1991), have been effective in changing cultural practices.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%